2012
DOI: 10.4161/auto.8.2.18618
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy can promote but is not required for epithelial cell extrusion in the amnioserosa of the Drosophila embryo

Abstract: During Drosophila embryogenesis the majority of the extra-embryonic epithelium known as the amnioserosa (AS) undergoes programmed cell death (PCD) following the completion of the morphogenetic process of dorsal closure. Approximately ten percent of AS cells, however, are eliminated during dorsal closure by extrusion from the epithelium. Using biosensors that report autophagy and caspase activity in vivo, we demonstrate that AS cell extrusion occurs in the context of elevated autophagy and caspase activation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Quantification of LC3 A/B fluorescent intensity showed that K-Ras V12 extruding cells had consistently higher numbers of puncta (~2300 mean fluorescent intensity per 20 cells), compared to their non-extruding neighboring cells (~800 mean fluorescent intensity per 20 cells). The LC3 A/B increase in extruding cells may be similar to that seen in extruding cells in Drosophila amniosera prior to extrusion [20]. Extruding K-Ras V12 may have higher levels of autophagy than either wild type extruding or unextruding K-Ras V12 cells due to the fact that both K-Ras V12 signaling and extrusion signaling promote autophagy (as seen in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Quantification of LC3 A/B fluorescent intensity showed that K-Ras V12 extruding cells had consistently higher numbers of puncta (~2300 mean fluorescent intensity per 20 cells), compared to their non-extruding neighboring cells (~800 mean fluorescent intensity per 20 cells). The LC3 A/B increase in extruding cells may be similar to that seen in extruding cells in Drosophila amniosera prior to extrusion [20]. Extruding K-Ras V12 may have higher levels of autophagy than either wild type extruding or unextruding K-Ras V12 cells due to the fact that both K-Ras V12 signaling and extrusion signaling promote autophagy (as seen in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…2D, F) suggesting an early onset of apoptosis. To visualize the effects of losses or gains of Egfr signaling on AS apoptosis in live embryos, we used the caspase sensor Apoliner [97], [98]. Apoliner consists of a monomeric red fluorescent protein (RFP) tethered to EGFP by a caspase-sensitive linker [97].…”
Section: Resultsmentioning
confidence: 99%
“…The amnioserosa is an extraembryonic tissue, and suffers histolysis in several forms: anoikis, autophagy, and apoptosis Toyama et al, 2008;Teng and Toyama, 2011;Cormier et al, 2012). For the lateral epidermis to completely surround the embryo, the two sets of lateral epidermal sheets must change shape and stretch over the amnioserosa toward the dorsal midline, and finally form a scarless continuum.…”
Section: Embryonic Dorsal Closurementioning
confidence: 99%
“…In this last, the mutant phenotype is more extreme, as the dorsal hole occupies the complete dorsal aspect of the cuticle, whereas the basket mutant cuticle showcases a hypomorphic condition, where some degree of closure (in the dorsal posterior aspect) is accrued. Subsequent quantitation of the phenomenon and, again, laser ablation studies showed that closure indeed would still happen in perturbed amnioserosal cell delamination and autophagy (Muliyil et al, 2011;Cormier et al, 2012). Data from in vivo microscopy analyses, laser ablation experiments and biophysical modeling led to the formulation of alternative hypotheses where amnioserosa cells, pulsing rythmically and periodically, generated also part of the force needed for closure (Solon et al, 2009;Blanchard et al, 2010).…”
Section: Embryonic Dorsal Closurementioning
confidence: 99%